y=9x=3
it equals ......
y= 3.334
Chat with our AI personalities
-9x+6=y (swap over +6 and y) -9x-y=-6 (when u move numbers or letters over d equal sign u need 2 change signs) 9x+y=6 (chaned all signs) y= 6-9 y= -3 9x+y=6 9x+-3=6 9x=6+3 9x=9 x=9(divided by) 9 x=1 9x+y=6 9+-3=6 So the ordered pair is (1,-3)
9x-3y=63 7x-3y=45 -3y=63-9x -y=21-3x y=-21+3x 7x-3(-21+3x)=45 7x+63+9x=45 7x+9x=45-63 16x=-18 x=-1.125 y=-21+3(-1.125) y=-24.375 (-1.125,-24.375)
3x-3y=-9 and 9x-9y=-27 both simplifies to x-y=-3.
2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9
9x + 3y = -54 3y = -9x - 54 y = -(3x + 18) Therefore, the y-intercept of this equation is y=-18.